Differentiated Learning Strategies and Their Relationship to Interest and Mathematics Learning Outcomes at SDN Kaliwatubumi - Arina Fatwasrie; Titi Anjarini; Nurhidayati Nurhidayati (Green Publisher Indonesia, 2025)
This study was conducted to identify gaps in the literature related to the application of differentiated learning strategies in mathematics subjects, especially at SDN Kaliwatubumi with suboptimal learning conditions. Although the importance of this strategy has been widely discussed, there are still mistakes in its implementation so that its effectiveness has not been maximized. The research method used is a qualitative method. Research activities are carried out by exploring information related to differentiated learning at the research location, disclosing specific and detailed field data. The data collection techniques in this study are interviews, observations, and documentation. Structured interviews are conducted with classroom teachers to obtain data. The study successfully developed a UN (Sustainably Differentiated Learning) scheme that involves continuous stages, such as needs analysis, action plans, teacher training, implementation, and reflection, designed to increase students' interest and learning outcomes in a sustainable manner. The findings show that the UN is effective in improving the quality of mathematics education, both at SDN Kaliwatubumi and at the level of basic education in Indonesia in general. The implication of this study is the need for continuous evaluation so that the implementation of the UN can be optimized. This scheme also makes a significant contribution to the development of adaptive and inclusive mathematics learning methodologies, so that it can be applied more widely in other schools with similar conditions.